PENGARUH ABU VULKANIK GUNUNG SINABUNG DAN BATUAN FOSFAT DALAM BENTUK NANOPARTIKEL TERHADAP RETENSI P, DELTA pH, DAN KEJENUHAN BASA PADA ANDISOLS CIATER, JAWA BARAT - Arfin, Mahfud; Yuniarti, Anni; Dahliani, Dewi (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
Andisols is a soil that develops from pyroclastic materials of volcanic eruption with the high P-Retention (85% or more). The aim of this research is to know the effect between the ameliorant of Sinabung volcanic ashes with the ameliorant of phosphate rock in nanoparticle form towards the P-retention, Delta pH and the base saturation on Ciaters Andisols, West Java. A randomized complete block design factorial with two factors was used in this research. The first factor is the volcanic ash and the second factor is phosphate rock which consists of four levels each amount of 0%, 2,5%, 5%, 7,5% with three replications. The result of this research showed that there was an interaction between the giving of volcanic ashes and the phosphate rock in nanoparticle form on the delta pH with the base saturation in the 1st month and also there was an independent effect on the P-retention with the base saturation in the 4th month. Combination of volcanic ashes with phosphate rock in nanoparticle form which is the dose combination of 2,5% each increased the delta pH in the 4th month incubation. The dose combination of volcanic ashes 7,5% with phosphate rock 5% increased the base saturation in the 1st month incubation. Volcanic ashes and phosphate rock each 7,5% decreased the P-Retention in the 1st month incubation.